Three Byte-Based Mutual Authentication Scheme for Autonomous Internet of Vehicles - Adil, Muhammad; Ali, Jehad; Attique, Muhammad; Jadoon, Muhammad Mohsin; Abbas, Safia; Alotaibi, Sattam Rabia; Menon, Varun G.; Farouk, Ahmed (IEEE Transactions on Intelligent Transportation Systems, 2022)
In this paper, we present a three-byte-based Media Access Control (MAC) protocol to resolve the mutual authentication problem in an Autonomous Internet of Vehicles (AIoV) network. Initially, the network architecture is divided into two chains, i.e. the local and public chain, wherein the local chain the authentication and communication process is controlled by Cluster head (CH), while in the public chain it is controlled by the base station (BS). The proposed paradigm uses the 48-bit MAC address of the vehicle's embedded sensors for authentication, with the ability to alter the authentication parameters by triggering the last three bytes (24 bits) of the MAC address with a predetermined time interval. Persistent triggering of the last three bytes of an AIoV's MAC address guarantees its integrity in the network because only legal vehicles are capable of initiating and validating the authentication request with the other vehicles in the network. Initially, the MAC addresses of all AIoVs are registered with the BS in the public chain through the concerned CH. Likewise, the MAC-address triggering of registered AIoVs is carried out in the BS with a defined time period and broadcasted in the public chain, which is further distributed through CHs in the local chain. Most of the computation is supervised by BS and CH in the public and local chains respectively, which minimize the client-side authentication complexity and enhances network efficiency in terms of authentication with 98.3% detection rate, communications, and computing costs, along with 11% improvement in the latency, 15% improvement in packet loss ratio (PLR), and throughput.
Keywords: Autonomous internet of vehicle; Data preservations; Device authentications; Device-to-device authentication.; Media access control address; Register; Routing-protocol; Security; Security and data preservation; Vehicular Adhoc Networks (VANETs); Autonomous Internet of Vehicles; device-to-device authentication; routing protocols; security and data preservation